2020
DOI: 10.1371/journal.pone.0231204
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and burden of bronchiectasis in a lung cancer screening program

Abstract: Introduction The prevalence of bronchiectasis in the general population and in individuals undergoing lung cancer screening with low dose computed tomography (LDCT) is unknown. The aim of this study is to estimate the prevalence and impact of bronchiectasis in a screening lung cancer program. Methods 3028 individuals participating in an international multicenter lung cancer screening consortium (I-ELCAP) were selected from 2000 to 2012. Patients with bronchiectasis on baseline CT were identified and compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…Advanced age appears to be associated with an increase in genomic instability resulting from reduced DNA damage repair capacity 28 . In addition, studies have shown that bronchiectasis seems to be directly related to the emergence of cancers, at a frequency ranging from 0.2–16%, and that age helps to increase these rates among bronchiectasis 23 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Advanced age appears to be associated with an increase in genomic instability resulting from reduced DNA damage repair capacity 28 . In addition, studies have shown that bronchiectasis seems to be directly related to the emergence of cancers, at a frequency ranging from 0.2–16%, and that age helps to increase these rates among bronchiectasis 23 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of bronchiectasis in participants in lung cancer screening programs has been analyzed in the two different studies of I-ELCAP subcohorts (Cai Q.Y.N., Yip R., Triphuridet N., Yankelevitz D.F., Henschke C.I., Clinical Findings of Participants with Severe Bronchiectasis on Baseline Low-dose CT Screening for Lung Cancer). 22 Using different scales, 11% and 23% of the participants from Pamplona and New York, respectively, had bronchiectasis on their LDCT. In the Spanish study, individuals with bronchiectasis more frequently had lung nodules and a greater proportion was not cancer.…”
Section: Possible Pitfalls In the Detection Of Malignancy In Respirat...mentioning
confidence: 99%
“…In the Spanish study, individuals with bronchiectasis more frequently had lung nodules and a greater proportion was not cancer. 22 These differential diagnoses led to an increased level of follow-up imaging studies or even invasive diagnostic procedures. Therefore, often, in clinical practice-when infection is a possible differential diagnosis-antibiotic treatment and a follow-up CT are recommended.…”
Section: Possible Pitfalls In the Detection Of Malignancy In Respirat...mentioning
confidence: 99%
“…Tri familije adhezionih molekula učestvuje u ovom procesu: selektini, integrini CD 11/CD 18, i super familija imunoglobulina uključujući intracelularni adhezioni molekul (ICAM) 1 i vaskularni adhezioni molekul (VCAM)1 i CD 47. Adherirani neutrofili migriraju u disajne puteve pod dejstvom hemotaktičnih faktora (IL 8, LT B4) [17,18]. Aktivirani neutrofili luče brojne proteaze, uključujući neutrofilnu elastazu, katepsin G i proteinazu 3.…”
Section: ćElije Infalamcije U Bronhiektazijamaunclassified